The impact of customer relationship management on the granting of consumer and retail credit: a case study of CAL Bank (Gh) Ltd. - Akosah, Abraham Bkrumah (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of the Degree of Master of Business Administration,